2018
DOI: 10.2146/ajhp180031
|View full text |Cite
|
Sign up to set email alerts
|

Association between prothrombin time and bleeding in hospitalized patients receiving rivaroxaban

Abstract: In hospitalized patients receiving rivaroxaban who had coagulation tests performed, a PT of ≥30 seconds was associated with a higher risk of bleeding. Hypoalbuminemia was also associated with bleeding in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Although based on small numbers, the work suggests that those at highest risk with low DOAC concentrations experience events. Woodruff et al (2018) investigated the association between prothrombin times and bleeding in hospitalised patients receiving rivaroxaban. In their single-centre retrospective cohort study, adult inpatients who had the prothrombin time (PT) measured within 24 h of rivaroxaban administration were identified and a multivariate logistic regression model was used to quantify the association between PT and bleeding events.…”
Section: What Can Be Learnt From the Clinical Trials Regarding Doac Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Although based on small numbers, the work suggests that those at highest risk with low DOAC concentrations experience events. Woodruff et al (2018) investigated the association between prothrombin times and bleeding in hospitalised patients receiving rivaroxaban. In their single-centre retrospective cohort study, adult inpatients who had the prothrombin time (PT) measured within 24 h of rivaroxaban administration were identified and a multivariate logistic regression model was used to quantify the association between PT and bleeding events.…”
Section: What Can Be Learnt From the Clinical Trials Regarding Doac Cmentioning
confidence: 99%
“…In their single‐centre retrospective cohort study, adult inpatients who had the prothrombin time (PT) measured within 24 h of rivaroxaban administration were identified and a multivariate logistic regression model was used to quantify the association between PT and bleeding events. In total, 199 patients were identified, of which 41 experienced a bleeding event; patients with a PT ≥ 30 s were more likely to have experienced a bleeding event, than those with a PT < 30 s (Woodruff et al , ). This study however does not report the exact time after dose that the PTs were measured, so it is difficult to know if like is being compared to like (in terms of time after dose) and therefore, it is again difficult to draw any firm conclusions from this.…”
Section: What Evidence Has Been Reported From the Real‐world?mentioning
confidence: 99%
“…28 Woodruff et al compared PT levels measured within 24 hours of taking rivaroxaban in a retrospective study (n ¼ 199) and were able to conclude that patients with PT >30 seconds (twice the upper limit of the normal PT of the assay used in the study) had a threefold higher bleeding risk compared with those with PT <30 seconds (p ¼ 0.006). 29 In a recent study involving 94 patients, Sakaguchi et al showed that the rivaroxaban peak concentration was an independent predictive bleeding risk factor (p ¼ 0.012). Trough levels were not associated with bleeding in this study.…”
Section: Rivaroxabanmentioning
confidence: 98%
“…76 Finally, hypoalbuminemia, a frequent condition in the elderly, has also been associated with higher rates of bleeding in rivaroxaban-taking patients. 29 Elderly patients are a fragile population in which bleeding events could be more frequent for those taking DOACs. Severity and consequences of bleeding events are likely to be worse in older patients due to frailty and comorbidities.…”
Section: Elderly Patientsmentioning
confidence: 99%
See 1 more Smart Citation